Pengaruh Temperatur Tehadap Produksi Bio-oil Bungkil Kemiri Sunan Menggunakan Reaktor Pirolisis Rotary Bed - Wiraharja, I Nyoman Jaya Prakarsa; Winaya, I N. Suprapta; Tenaya, I G.N.P. (Teknik Desain Mekanika, 2021)
Abstract Energy reserves produced by fossil fuels are estimated to be depleting as time passes by and the technology advances, resulting to the need for new renewable energy sources derived from biomass. However, processing sunan candlenut biodiesel by pressing method produces waste in the form of sunan candlenut cake which still contains oil that cannot be taken out through the press process. One way to take out this oil is through the pyrolysis process. In the pyrolysis process, the higher temperature causes the sunan candlenut fuel to be completely decomposed so as to produce more gas and condensate with a relatively low amount of charcoal. This study therefore sets out to assess the effect of temperature on the mass production of bio-oil (condensate) through rotary bed pyrolysis. In this study, it is expected that the produced mass of condensate will increase along withwthewincrease in temperature. The reactor was operated atwtemperatures of 250°C, 350°C, 450°C, and 550°C. The research test result showed that the temperature of 550°C has better results compared to other temperature variations. Thewhigher the temperature, thewhigher the pH value of the condensate andwthe lower the flash point and fire point temperatures. Keywords : Temperature, rotary pyrolysis, bio-oil (condensate), sunan candlenut